The impact of ocular tuberculosis on vision after two months of intensive therapy - Oliveira,Suzana Batista Vereza de (2018)
ABSTRACT Tuberculosis is an infectious disease of global importance with major economic and social burden accounting for 25% of all avoidable deaths in developing countries. Extrapulmonary involvement may occur either in association with clinically apparent pulmonary tuberculosis or in isolation. This cross-sectional descriptive study aimed to evaluate the impact of ocular tuberculosis in visual acuity at baseline and after two months of intensive anti-tuberculous therapy. A sample of 133 pulmonary tuberculosis patients, seven disseminated tuberculosis, and three pleural tuberculosis patients was evaluated. All patients underwent routine ophthalmic evaluation, including assessment of visual acuity, biomicroscopy, applanation tonometry, indirect ophthalmoscopy, and fluorescent angiography as appropriate. None of the patients had impaired visual acuity due to tuberculosis. A rate of 4.2% (6/143) of ocular involvement was found. None of the patients with ocular involvement were HIV-infected. Of the six patients with ocular involvement, five met the diagnostic criteria for probable and one for possible ocular lesions. As for the type of ocular lesions, two patients had bilateral findings: one had sclerouveitis and the second had choroidal nodules. The other four patients presented with unilateral lesions: peripheral retinal artery occlusion in the right eye (one case), choroidal nodules in the left eye (one case), and choroidal nodules in the right eye (two cases). Patients progressed favorably after two month of intensive therapy, with no significant reduction in vision.